Conocimientos y currículo en la educación matemática - Ruiz, Angel (2010)
Central issues of the curriculum for the initial formation of Mathematics Teachers are tackled and we propose a model for the description of the different knowledge components that it must include. There is propped up the role of the Pedagogical Content Knowledge PCK, and characteristics so much of this one PCK as of the Mathematics that specifically must include these curricula are proposed.